Walk Band for Better Learning: An Android-Based Music Module to Enhance Student Outcomes - Armanto, Firdaus Budhi; Sitompul, Nurmida Catherine; Nurjati, Nunung (Jurnal Edutech Undiksha, 2025)
The main problem in music learning at the high school level is the limited availability of musical instruments and the absence of representative teaching materials that can integrate theory and practice in a balanced way. This condition hampers students’ ability to apply musical knowledge optimally, thereby necessitating the innovation of digital technology-based teaching materials. This study aims to develop and evaluate an Android-based music learning module using the Virtual Instrument Walk Band application to enhance music education for high school students. The instructional design model ADDIE was employed to guide the development process. Data collection techniques included expert validation, small- and large-group trials, as well as pre- and post-tests to assess effectiveness. Expert validation indicated high validity in terms of content (93.33%), design (91.43%), and media (94.28%). Field testing with small and large student groups yielded positive responses, with mean scores of 87.5% and 88.51%, respectively. A paired-sample t-test was conducted to analyze the module’s effectiveness, revealing a statistically significant improvement in student learning outcomes (t = -8.290, p < 0.001). These findings demonstrate that the module is both feasible and effective in supporting critical thinking and engagement in music learning. This study highlights the potential of integrating virtual instrument applications into instructional design to address the lack of practice instruments and teaching materials in music education.